Molar shape variability in platyrrhine primates. Issue 99 (October 2016) - Nova Delgado, Mónica; Galbany, Jordi; Pérez-Pérez, Alejandro
Abstract: Recent phylogenetic analyses suggest that platyrrhines constitute a monophyletic group represented by three families: Cebidae, Atelidae, and Pitheciidae. Morphological variability between and within these three families, however, is widely discussed and debated. The aim of this study was to assess molar shape variability in platyrrhines, to explore patterns of interspecific variation among extant species, and to evaluate how molar shape can be used as a taxonomic indicator. The analyses were conducted using standard multivariate analyses of geometric morphometric data from 802 platyrrhine lower molars. The results indicated that the interspecific variation exhibited a highly homoplastic pattern related to functional adaptation of some taxa. However, phylogeny was also an important factor in shaping molar morphological traits, given that some phenotypic similarities were consistent with current phylogenetic positions. Our results show that the phylogenetic and functional signals of lower molar shape vary depending on the taxa and the tooth considered. Based on molar shape, Aotus showed closer similarities to Callicebus, as well as to some Cebidae and Ateles-Lagothrix, due to convergent evolutionary trends caused by similar dietary habits, or due to fast-evolving branches in the Aotus lineage, somewhat similar to the shape of Callicebus and Cebidae.